Islamic Teachers' Educational Idealism Based On Al-Qur'an Surah Luqman - Ahmad Zuhri (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Idealism plays a significant role in the world of education. Education is more than just trying to achieve learning outcomes; it is also about how to obtain results or learning processes in children. Thus, in education, there must be a balance between the process and the learning outcomes. An ideal education is thought to be capable of serving human growth in all aspects, including spiritual, intellectual, imaginative, and scientific growth. The Qur'an is a guide for Muslims that contains guidelines for living in the world. Al-Qur'an is a book that can answer all of the world's problems, including educational problems, which are also explained in it. Surah Luqman verses 12-19 contain many of these educational values. Educational values based on Surah Luqman form the foundation of education and should serve as a guideline for all Muslims. The authors conducted library research in this study, which focused on library books and other literature. Based on the research objectives, it includes basic research, i.e. research to broaden and deepen theoretical knowledge. The study's findings show that the idealism of Islamic education in the Qur'an basically directs humans to know their true identity and function in accordance with it. Educational idealism focuses on five important issues in human life: monotheism education, worship education, ethics or morals education, mental education, and life management education. Thus, it is hoped that humans will be able to develop themselves optimally in order to achieve happiness in their lives both now and in the future.